Rasio Neutrofil Limfosit Mengindikasikan Derajat Keparahan Covid-19 - Leny Luckytasari; Ratna Dewi Indi Astuti Astuti; Usep Abdullah Husin (Bandung Conference Series: Medical Science, 2023)
Abstract. COVID-19 has symptoms that vary from asymptomatic to severe, this is because each individual's body's immune response is different. The higher the inflammatory response, the more severe the symptoms of COVID-19. One indicator of inflammation is the NLR (Neutrophil Lymphocyte Ratio). The aim of this study is to analyze the differences in NLR in patients with moderate and severe clinical degrees of COVID-19. This research method is observational with a cross-sectional design using a simple random sampling technique. Data is taken from the medical records of COVID-19 patients who were hospitalized at RS-Al Islam Bandung for the period June-July 2021, obtained 605 medical records that met the inclusion criteria and 100 samples were taken to meet the minimum sample size. Data analysis is performed using Mann Whitney and obtained a p value of 0.000 (<0.05). This shows that there is a significant difference in NLR in the moderate and severe clinical degree groups. Patients with moderate clinical degree of COVID-19 had a NLR of 3.6, while patients with severe clinical degrees had an NLR of 9. A high NLR value was affected by an increase in the number of neutrophils and a decrease in the number of lymphocytes. An increase in the number of neutrophils is caused by an increase in the inflammatory response, while a decrease in the number of lymphocytes indicates damage to the immune system, so a high NLR value can indicate an increase in the severity of the disease. Abstrak. COVID-19 memiliki gejala yang bervariasi dari tidak bergejala hingga berat, hal ini disebabkan karena respon imun tubuh setiap individu berbeda. Semakin tinggi respon inflamasi maka menyebabkan gejala COVID-19 yang lebih berat. Salah satu indikator inflamasi adalah NLR (Neutrophil Lymphocyte Ratio). Tujuan penelitian ini yaitu untuk menganalisis perbedaan NLR pada pasien COVID-19 derajat klinis sedang dan berat. Metode penelitian ini yaitu observasional dengan desain potong lintang menggunakan teknik pemilihan sampel simple random sampling. Data diambil dari rekam medis pasien COVID-19 yang dirawat inap di RS-Al Islam Bandung periode Juni─Juli 2021, didapatkan 605 rekam medis yang memenuhi kriteria inklusi dan diambil 100 sampel untuk memenuhi jumlah minimal besar sampel. Analisis data dilakukan dengan menggunkan Mann Whitney didapatkan p value sebesar 0.000 (< 0.05). Hal ini menunjukkan terdapat adanya perbedaan NLR yang signifikan pada kelompok derajat klinis sedang dan berat. Pada pasien COVID-19 derajat klinis sedang memiliki NLR sebesar 3,6, sedangkan pada pasien derajat klinis berat memiliki NLR sebesar 9. Nilai NLR yang tinggi dipengaruhi oleh peningkatan jumlah neutrofil dan penurunan jumlah limfosit. Peningkatan jumlah neutrofil disebabkan karena peningkatan respon inflamasi, sedangkan penurunan jumlah limfosit mengindikasikan adanya kerusakan sistem imun, sehingga nilai NLR yang tinggi dapat mengindikasikan peningkatan keparahan penyakit.